Radiation-Induced Segregation in W-Re: From Kinetic Monte Carlo Simulations to Experimental Validation - Lloyd, M; Moody, M; Armstrong, D; Nguyen, D (University of Oxford, 2019)
Data for figures 1-14 for Radiation-Induced Segregation in W-Re: From Kinetic Monte Carlo Simulations to Experimental Validation. Python is needed to plot the figures and Ovito for visualisation.